SPEECH FUNCTIONS OF THE MAIN CHARACTER, STRANGE,’S UTTERANCES IN DOCTOR STRANGE FILM - Shafira, Naila; Sari, Retno Purwani (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2020)
This study aims to explain social functions carried by a certain utterance. Situational context initiates a speaker with evaluating and deciding which appropriate utterances may be uttered, and those mostly performs varied speech functions. In Doctor Strange film, especially, some different functions are debatable being intended and communicated. This study, though, describes potential proposed functions and their implication in conversational communication by identifying and analyzing: (1) types of speech functions; and (2) their implications. The adaptation of Holmes’ perspectives was due to those aims. Descriptive method with qualitative approaches was implemented through observation, note taking, transcription techniques of data collection and descriptive technique of data analysis. The result of this study shows that Stranger’s utterances perform Holmes’s six types of speech functions: 24 expressive, 35 directive, 80 referential, 12 metalinguistic, 6 phatic, and 5 poetic. These facts imply that identified functions represent social context in which the utterances are uttered. The context has determined the choice of utterances.